Analysis of the Cases of Witch Hunting and its Reporting in Two Regional Newspapers of Jharkhand - Rani, Pratibha (Journal of Advanced Research in Journalism & Mass Communication, 2022)
In India, murders under the pretext of witchcraft is reported every third day as per the report of National Crime Report Bureau (NCRB). Among various states, the situation is worst in Jharkhand as it tops the list with 575 murders between 2001 to 2019. Being the fourth pillar of democracy, media holds a responsibility to guide the process of social change. The onus is on media to objectively and truthfully report the cases of witch-hunting to facilitate awareness and draw the attention of public and the government towards such heinous acts. However, as generally observed, the discussion and coverage of such issues in print media are often scarce. Therefore, the present study explores the cases of crimes of witchcraft and witch hunting. It analyzes the content and reporting style of the news reports on the same in two leading newspapers of Jharkhand. To achieve these goals, the research employed the method of content analysis while dealing with various important variables including regions of crimes, information regarding victims, action against culprits, space dedicated to such reports in newspapers, page of news publication, etc. The findings after the analysis of the NCRB reports of eastern states from 2001-2019 demonstrates that Jharkhand constitutes 20.55% of the total witch hunting murders in India, with the maximum number of cases in the districts of Gumla, Khunti and Giridih. Besides, it was also found out that the reporting of such cases in the local newspapers of Jharkhand is mostly shallow and insufficient, with only 50% of the cases being reported on inner pages (i.e, page 8, 10 and 12) with very little space dedicated to these news stories. The study is instrumental to estimate the role of media, especially newspapers in addressing and eradicating the crimes pertaining to witchcraft.